Tekst, sekvens og heterogenitet. Introduktion til J.-M. Adams teori om teksttyper - Frandsen, Finn (HERMES - Journal of Language and Communication in Business, 1998)
The present paper gives a critical introduction to the theory of text types or text sequences elaborated by the French text linguist Jean-Michel Adam. The first part of the paper presents the overall theoretical framework for Adam’s research within stylistics and text linguistics. The second part of the paper gives a more detailed discussion of Adam’s answers to what may be defined as the four most crucial questions within text type research, that is: a) the number of text types which can be identified (the classification problem), b) the relation between text types within individual texts, c) the relation between text types and linguistic features and d) the relation between text types and their communicative function (the interaction between form and function). L’objectif de la linguistique textuelle est simple : poursuivre l’analyse lin-guistique au-delà de la phrase complexe et des seuls couples de phrases et, si difficile que cela paraisse, accepter de se situer aux frontières du linguistique dans le but de rendre compte de l’hétérogénéité de toute composition textuelle.